Parkes Weber syndrome. Case report. - Sariwana, Dr.; Tabri, F.; Widita, W.; Wahab, S.; Latief, N.; Budhiani, S. (European Journal of Pediatric Dermatology, 2019)
Parkes Weber syndrome is a rare vascular malformation characterized by arteriovenous malformations, varicose veins and soft tissue hypertrophy of a limb. The diagnosis is confirmed by color doppler ultrasound that highlights vascular malformations, standard X-ray showing the limb volume variation and possible osteolytic lesions, and angiography or magnetic resonance imaging that make evident the damage of the blood vessels and the hypertrophy of the soft tissue. A case characterized by painful vascular malformations and hypertrophy of the left lower limb was here described for its rarity and to underline the need for appropriate investigations aimed at avoiding diagnostic errors and preventing further aggravation of symptoms.